Synergy in Early Warning Conterence: Background - Schmeidl, Susanne; Adelman, Howard (Refuge: Canada's Journal on Refugees, 1997)
This article has information on theconference Synergy in Early Warningorganized recently by the Prevention/Early Warning Unit in Toronto,Canada. Included are: background onthe issues, a brief outline with the abstractsof the papers delivered and thecontact addresses of the authors.